Finite element modelling of non-linear thermal buckling analysis of different multilayer offshore pipelines (Journal of Naval Architecture and Marine Engineering, 2025)
Offshore pipelines operating under harsh environmental conditions of high temperature and pressure are susceptible to thermal buckling. The presence of initial imperfections in a pipeline significantly increases its susceptibility to global buckling failure when exposed to thermal stresses and internal pressure. This risk is further exacerbated by temperature gradients across the pipeline's wall, primarily driven by heat transfer between the petroleum products and the surrounding environment. This research utilizes the finite element (FE) analysis software ANSYS to investigate the effect of radial temperature gradients and initial imperfections on the thermal buckling behavior of various multilayer offshore pipeline designs, including lined, sandwich (SW), and pipe-in-pipe (PIP) configurations. The FE model employs a sequentially coupled analysis of heat transfer and nonlinear thermal buckling. Buckling temperatures are determined for each configuration and compared with those of a conventional single-layer (SL) pipeline. The impact of insulation on pipeline performance is assessed through an analysis of radial temperature and Von Mises stress profiles. The results demonstrated that the PIP configuration exhibited the most significant improvement in critical buckling temperature, surpassing both the single-layer and other multilayer pipelines. In contrast, the lined pipe's buckling temperature is nearly identical to that of the single-layer pipeline. The results further demonstrate that the buckling temperature of the multilayer pipelines is influenced by the temperature variation across the pipeline's radius, the properties of the insulation layers, and the initial imperfections of the pipelines.Journal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 165-181